Unequal in Life but Equal in Death? The Mortuary Evidence for Social Stratification in the Ubaid Polities - Kopanias, Konstantinos; Barlagianni, Giota (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2019)
The archaeological evidence is inconclusive as to whether the Ubaid society was egalitarian or not. The almost complete absence of prestige goods and the rarity of imported raw materials in the Ubaid settlements appear to indicate the existence of an unstratified society. On the other hand, it is possible that an elite did indeed exist, but left almost no trace in the material culture. A re-evaluation of the mortuary practices in the Ubaid period offers some insight on this subject. A closer look at the archaeological evidence shows little variation concerning the quantity and quality of grave offerings. This means that the mortuary evidence too offers no direct clues for the existence of a stratified society in the Ubaid polities. Rather, the funerary practices indicate that in the Ubaid period there was no symbiotic relation between the living and the dead, as was witnessed in both previous and later periods in Mesopotamia. After the completion of the funerary rites, a deceased person was no longer considered to be a threat to or an asset for the community.